2007
DOI: 10.1016/j.neuroscience.2006.08.074
|View full text |Cite
|
Sign up to set email alerts
|

Cockayne syndrome exhibits dysregulation of p21 and other gene products that may be independent of transcription-coupled repair

Abstract: Cockayne syndrome (CS) is a progressive childhood neurodegenerative disorder associated with a DNA repair defect caused by mutations in either of two genes, CSA and CSB. These genes are involved in nucleotide excision repair (NER) of DNA damage from ultraviolet (UV) light, other bulky chemical adducts and reactive oxygen in transcriptionally active genes (transcription coupled repair, TCR). For a long period it has been assumed that the symptoms of CS patients are all due to reduced TCR of endogenous DNA damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Overexpressed neural genes included myelin basic protein, Synaptogyrin 3 (which plays a role in learning and memory), neogenin (which plays a role in axonal guidance in the nervous system), and the potassium voltage-gated channel, shaker-related subfamily, ␤ member 1. Previous results have also shown increased levels of the p21 cell cycle regulatory protein and underexpression of collagen 15a1 in human fibroblasts from CS patients (27).…”
Section: Apoptosis and Neurogenesis In The Cerebellum Of Csbmentioning
confidence: 71%
See 1 more Smart Citation
“…Overexpressed neural genes included myelin basic protein, Synaptogyrin 3 (which plays a role in learning and memory), neogenin (which plays a role in axonal guidance in the nervous system), and the potassium voltage-gated channel, shaker-related subfamily, ␤ member 1. Previous results have also shown increased levels of the p21 cell cycle regulatory protein and underexpression of collagen 15a1 in human fibroblasts from CS patients (27).…”
Section: Apoptosis and Neurogenesis In The Cerebellum Of Csbmentioning
confidence: 71%
“…Mutations in the XPD component of the transcription factor TFIIH, with which CS proteins interact, also result in many transcriptional defects, including reduced responses to nuclear receptors (60,61), dysregulation of peroxisome proliferator-activated target genes (62), vitamin D receptor-responsive genes (63), and thyroid hormone-responsive genes leading to hypomyelination (64). Both CSA and CSB cells also exhibit down-regulation of collagen 15a1 expression and dysregulation of p21 (27), and CSB plays a role in chromatin structure (13).…”
Section: Are Dna Lesions Important For Neurodegeneration In Cs?mentioning
confidence: 99%
“…Thus, an alternative interpretation of the data is that the observed γ-H2AX induction, particularly outside of S-phase, is not entirely in response to DSB formation. Recently, it has been reported that following ultraviolet radiation γ-H2AX does not necessarily reflect DSB during the G1 phase of the cell cycle [42], as well as in growtharrested cells in G0 [24]. Interestingly, ICL-forming agents have been reported to generate ssDNA foci that depend on NER, and ssDNA resulting from impaired gap-filling during nucleotide excision repair has recently been reported to be associated with γ-H2AX induction [24,43].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, XPG was recently identified as a protein required for maintaining the integrity of the TFIIH complex, and therefore also engaged in the transcription process (20). Even though the contribution of the DNA repair deficiency to the clinical features of patients with XP, CS, or XP/ CS is irrefutable, studies have shown a clear dysregulation of a variety of transcriptional pathways, which may also contribute to the clinical phenotype of these patients (21)(22)(23)(24)(25)(26)(27). Interestingly, at the cellular level, XP/CS cells share with CS cells a sustained global transcriptional arrest after UV irradiation, which has been always explained by the inability of these cells to perform TCR (17,28).…”
mentioning
confidence: 99%